The Expositor's Bible commentary: Ephesians-Philemon V.12 - Longman, Tremper; Garland, David E. (Grand Rapids, Mich. : Zondervan, 2006)
"This is a complete revision of the Gold Medallion-winning commentary series. It is up to date in its discussion of theological and critical issues and thoroughly evangelical in its viewpoint."--Publisher description.
v. 1. Genesis-Leviticus -- v. 2. Numbers -- Ruth -- v. 3. 1 Samuel -- 2 Kings -- v. 4. 1 Chronicles-Job -- v. 5. Psalms -- v. 6. Proverbs-Isaiah -- v. 7. Jeremiah -- Ezekiel -- v. 8. Daniel-Malachi -- v. 9. Matthew-Mark -- v. 10. Luke-Acts -- v. 11. Romans-Galatians -- v. 12. Ephesians-Philemon -- v. 13. Hebrews-Revelation.
Includes bibliographical references.
Keywords: Bible -- Commentaries; Commentaries